Analisa Kontekstual Markus 7:1-23 Dalam Hubungan Dengan Peraturan Makanan Di Perjanjijan Lama - Jemmy C. Najoan (Jurnal Koinonia, 2021)
Mark: 15,19 often becomes a polemic in Christian circles related to the issue of annulment of laws about clean and unclean food in the Old Testament. The Christian view generally supports that Jesus abrogated the Old Testament dietary regulations. Not much discussion regarding the context analysis of this passage is done in Bahasa Indonesian. That is why, using the contextual analysis methods, this article analyzed the context of Mark 1-23 and looked the meaning of vv. 15 and 19. In addition, this article also looked at whether Jesus canceled the Old Testament related to clean and unclean. The result shows what Jesus meant about what came in did not make people unclean (v. 15) refers to general idea of eating food. What defiles is something thatcomes out of the heart. In a sense, impurity does not come from eating without washing hands. Regarding Mark's additional editorial "Thus he says all food is clean," the context shows that what Mark meant is not the annulment of clean and unclean rules. In fact, here, Mark was emphasizing that whether food is eaten by washing hands or not, it is clean and does not make people unclean. In addition, Jesus' criticism of the Pharisees and scribes by comparing God's traditions and laws shows that He was rebuking the guilt of these Jewish leaders who ignored God's word for the sake of their traditions. That is what happened in this case, Jesus was not abrogating God's commands in regard to clean and unclean.